Chronic Obstructive Pulmonary Disease as a Cardiovascular Diseases Risk Factor in Erbil - Goran Abubaker Osman; Halmat Authman Rasheed; Yousif Mohammed Younis; Newroz Khazi Aziz; Hemin Khlid Saber (Hawler Medical University, 2019)
Background and objectives: Chronic obstructive pulmonary disease (COPD) has been reported as the most common cause of morbidity and mortality all over the world. The present study aimed to investigate a possible link between chronic obstructive pulmonary dis-ease and increased risk of cardiovascular disease in Erbil, the Kurdistan Region of Iraq. Methods: A quantitative, case-control study was conducted on 159 patients with COPD as the case group and 159 adult people without COPD as control group. Case groups were patients who have COPD and admitted to the medical ward at Hawler Teaching Hospital and Rzgary Teaching Hospital. Control groups were those without COPD and went to City Park and Mala-fandy Primary Health Center. Data was collected from January 2018 to August 2018 through direct interview and using a questionnaire. A spirometer machine was used to confirm the diagnosis of COPD. Data analysis was carried out through descriptive statistics (frequency and percentage), skeunosis-kurtosis test, t-test, Mann-Whitney U test, Pearson's Chi-squared test, and univariate logistic regression. Results: Compared to the control group, patients with chronic obstructive pulmonary dis-ease were found to be at a significantly higher risk of developing hypertension, diabetes, ischemic heart disease, dyslipidemia, and lung cancer. Moreover, there was an inverse correlation between increased severity of chronic obstructive pulmonary disease and in-creased hypertension and stroke. In addition, chronic obstructive pulmonary disease, hypertension, diabetes, and dyslipidemia were found to be significant risk factors for ischemic heart disease. Conclusions: The risk of cardiovascular comorbidities was significantly higher in the patients with chronic obstructive pulmonary disease and there is a significant association between chronic obstructive pulmonary disease and cardiovascular comorbidities.